Factors Influencing Investors’ Investment Decisions in Crowdfunding Financial Technology (Case Study: Danamart Platform) - Dede Suryanto; Bernardus Yuliarto Nugroho; Nur Fatwa (Green Publisher Indonesia, 2026)
The rapid development of financial technology (fintech) in Indonesia has given rise to various innovative financing alternatives, one of which is Securities Crowdfunding (SCF), which provides capital solutions for Micro, Small, and Medium Enterprises (MSMEs) through digital crowdfunding platforms. As a relatively new investment instrument in Indonesia, SCF presents both opportunities and challenges for investors and prospective investors in making investment decisions. This research aims to determine the effect of Organizer (X1), Issuer (X2), Risk (X3), Securities (X4), on Investment Decisions (Y) of Investors / Potential Investors on the Danamart platform and the role of ALUDI to influence and increase the interest of Investors / Potential Investors to invest in crowdfunding services. The population in this study is the Investor / Potential Investor on the Danamart platform and the sample technique used in this study is random sampling. This research uses SPSS Version 29.00 software, analysis using quantitative and qualitative methods (mixed method) with descriptive analysis and hypothesis testing using binary logistic regression analysis. The results showed that: (1) Organizers have a significant effect on Investment Decisions. (2) Issuer has a significant effect on Investment Decisions. (3) Risk has a significant effect on Investment Decisions. (4) Securities have no significant effect on Investment Decisions. Simultaneously the Organizer (X1), Issuer (X2), Risk (X3), Securities (X4) variables have a significant effect on Investment Decisions as evidenced in the Omnibus Test of Model Coefficients table sig value. 0,001 < 0,05.